Illusions and delusions: relating experimentally-induced false memories to anomalous experiences and ideas - Corlett, Philip R.; Simons, Jon S.; Pigott, Jennifer; Gardner, Jenny M.; Murray, Graham K.; Krystal, John H.; Fletcher, Paul C. (Frontiers in Behavioral Neuroscience, 2009)
The salience hypothesis of psychosis rests on a simple but profound observation that subtle alterations in the way that we perceive and experience stimuli have important consequences for how important these stimuli become for us, how much they draw our attention, how they embed themselves in our memory and, ultimately, how they shape our beliefs. We put forward the idea that a classical memory illusion – the Deese-Roediger-McDermott (DRM) effect – offers a useful way of exploring processes related to such aberrant belief formation. The illusion occurs when, as a consequence of its relationship to previous stimuli, a stimulus is asserted to be remembered even when has not been previously presented. Such illusory familiarity is thought to be generated by the surprising fluency with which the stimulus is processed. In this respect, the illusion relates directly to the salience hypothesis and may share common cognitive underpinnings with aberrations of perception and attribution that are found in psychosis. In this paper, we explore the theoretical importance of this experimentally-induced illusion in relation to the salience model of psychosis. We present data showing that, in healthy volunteers, the illusion relates directly to self reported anomalies of experience and magical thinking. We discuss this finding in terms of the salience hypothesis and of a broader Bayesian framework of perception and cognition which emphasizes the salience both of predictable and unpredictable experiences..